Effect of chlorpyrifos and carbofuran on morphology, behavior and acetylcholinesterase activity of earthworm (Eisenia fetida) - YADAV, JYOTI; SINGH, DHARAMBIR; SHEFALI, SHEFALI (The Indian Journal of Agricultural Sciences, 2020)
Organophosphates (OP) and carbamates when applied in agricultural fields are the potential environmental polluters and toxicants for soil flora and fauna. Upon exposure to such chemical pesticides, morphology, behaviour and acetylcholinesterase (AChE) activity of earthworms (Eisenia fetida) is altered. The present study dealt with the comparative analysis of toxic effects induced by chlorpyrifos (OP) and carbofuran (carbamate) exposure on morphology, behavior and AChE activity using standard filter paper contact toxicity method. The LC50 of chlorpyrifos and carbofuran for 24 hr was 0.25% and 5.13%, respectively, marking chlorpyrifos as more toxic pesticide than carbofuran. The treated worms exhibited abnormal morphological symptoms such as excessive mucus secretion, depigmentation, deformity, loss of metameric segments and damaged clitellum. Variation in behaviour such as reduced activity, sluggish movements and flattened posture marked the stress induced due to pesticide toxicity even at lower doses. Restlessness along with jerky movements was observed on exposure to higher concentrations of chlorpyrifos, whereas lower concentrations resulted in avoidance behavior toward pesticide coated glass vials. Thereafter, worms were exposed to different concentrations of chlorpyrifos (0.13%, 0.25% and 0.38%) and carbofuran (2.57%, 5.13% and 7.70%) for 24h and 48h to assess sub-acute and acute toxicity effects of these pesticides on AChE. The enzyme activity after 48h was 94.14%, 60.21% and 40.44% for the worms exposed to 0.125%, 0.25% and 0.375% chlorpyrifos, respectively. The enzyme activity after 48h was 98.17%, 93.92% and 79.25% for the worms exposed to 2.57%, 5.13% and 7.70% carbofuran, respectively. Time and dose dependent significant (p